Development The Control System of Plastic Molding Injection Machine - Mashni, Ahmad; Adwan, Diya (جامعة بوليتكنك فلسطين - كلية الهندسة - مباني, 2017)
The plastic products of industrial products that are indispensable, where is consumed significantly, it is used in many areas of daily life; therefore there is a need to produce a tremendous amount of these products. But there are few problems related to the existing line: first difficulty in the maintenance operation and follow the wrong secondly the large size of the control panel and the large number of wires and finally the time and effort are not effective. We worked on the development of industrial technology, to improve the production line to overcome this problem. In this project the machine has been development in order to meet the required quality and production rated PLC integrate with HMI system has been apply .
Cd, 30135, اتمتة صناعية 3/2017 , no of pages 51, in the store
Keywords: plastic; Injection Machine